(untitled) (International Journal of Built Environment and Sustainability, 2019)
This paper aims to demonstrate the conservation process of historic underground water access or Payab by proposing a multistage decision-making design in Gonabad city, northeast part of Iran. The Payab was in the center axis of a street in the proposed development of a new road which appeared to be against the new construction. The challenge was to develop the new road in the central axis without disturbing much the historic structure in the location. Hence, a request was made to keep both the new road and the historic Payab structure with a design solution. In order to tackle the design solution requested, a qualitative methodology was designed by way of site surveys, site documentation, graphical analysis and interviews. The findings of the research demonstrated contradicting opinions among the governors-laypeople, youngers-elders and males and females about the historic structure. Based on the findings, it was proposed that a protective shield, which aimed to conserve the historic structure under the weight of the new road is required, with a new entrance to be provided through an adjacent sidewalk to achieve consensus among those of diverse ideas. As a conclusion, conservation projects as demonstrated in this paper, like any other conservation projects elsewhere are faced with budget limitation, poor planning and the support it needed. As the historic structure has been part of the local built environment, the integration with other architectural elements in the context is of paramount importance to support the sustainability of the local built environment.